2019
DOI: 10.1111/jth.14369
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of platelet factor 4 amino acids that bind pathogenic antibodies in heparin‐induced thrombocytopenia

Abstract: Many patients produce antibodies but few lead to heparin‐induced thrombocytopenia (HIT). Pathogenic epitopes are difficult to identify as HIT antibodies are polyclonal and polyspecific. KKO binding to platelet factor 4 (PF4) depends on 13 amino acids, three of which are newly observed. Five amino acids in PF4 can help distinguish pathogenic from non‐pathogenic antibodies. Summary BackgroundHeparin‐induced thrombocytopenia (HIT) is an adverse drug reaction that results in thrombocytopenia and, in some patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…Although the conditions shown here are obviously not suitable for clinical application, others may take advantage of these basic data to improve antigen‐based assays for aPF4/H Abs to better discriminate between platelet‐activating and nonplatelet‐activating aPF4/H Abs. Potential approaches beyond the experiments described here could be to combine changes in pH and salt with recombinant PF4 mutants and/or the use of different polyanions to generate complexes with PF4 . CD spectroscopy can be used as a tool to identify the magnitude of conformational changes of PF4 in such designed PF4/polyanion complexes as an approximation to identify test conditions for further assessment with clinical antibody samples.…”
Section: Discussionmentioning
confidence: 99%
“…Although the conditions shown here are obviously not suitable for clinical application, others may take advantage of these basic data to improve antigen‐based assays for aPF4/H Abs to better discriminate between platelet‐activating and nonplatelet‐activating aPF4/H Abs. Potential approaches beyond the experiments described here could be to combine changes in pH and salt with recombinant PF4 mutants and/or the use of different polyanions to generate complexes with PF4 . CD spectroscopy can be used as a tool to identify the magnitude of conformational changes of PF4 in such designed PF4/polyanion complexes as an approximation to identify test conditions for further assessment with clinical antibody samples.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the binding epitopes of HIT antibodies are non-contiguous and conformation-dependent 13 . Therefore, to identify the specific amino acid targets of VITT antibodies on PF4, we used alanine scanning mutagenesis and produced 70 unique recombinant PF4 mutants, each differing by a single amino acid 5 . We defined a critical binding amino acid as a corresponding PF4 mutant that caused a greater than 50% reduction in binding compared to wild-type PF4.…”
Section: Binding Site Of Vitt Antibodies On Pf4mentioning
confidence: 99%
“…While the epitopes involved in the binding of classical HIT antibodies to PF4 are partially known,[ 47 , 48 ] those involved in autoimmune HIT syndromes have not yet been documented, and might be very different. [ 49 ] However, it is not excluded that these IgG antibodies directed against other epitopes are also able to activate platelets. In addition, the fact that these cases were mainly reported in young women should question on the possibility that we are facing previously immunized women.…”
Section: Introductionmentioning
confidence: 99%